Effect of fiber content on single tow SiC minicomposite mechanical and damage properties using acoustic emission. Issue 13 (November 2015) - Almansour, Amjad; Maillet, Emmanuel; Ramasamy, Sivakumar; Morscher, Gregory N.
Abstract: Ceramic matrix composites (CMCs) are attractive materials for use in temperature-critical aerospace and nuclear applications. Relating the mechanical behavior and damage mechanisms of simple ceramic matrix minicomposites to health-monitoring techniques helps to understand the fundamentals of the mechanical response of CMCs. In this study, single-tow minicomposites with a silicon carbide (SiC) matrix deposited by chemical vapor infiltration, a boron nitride or a carbon interphase, and various types of SiC fibers were tested in tension at room temperature. Modal acoustic emission (AE) was used to determine the dependence of matrix cracking on the applied load. Crack density evolution was obtained using two AE-based methods: the established method using cumulative energy of AE events and a new technique based on speed of sound measurements.